Keabsahan Akta Berita Acara Rapat Umum Pemegang Saham Perseroan Terbatas yang Dibuat Melalui Media Elektronik - Tuasikal, Ahmad Umar Farhan (Universitas Negeri Malang, 2021)
This study aimed to analyze the authority of a notary in making the minutes of the general meeting of shareholders of a limited liability company through electronic media and the legality of a notary deed related to the signing of a general meeting of shareholders of a limited liability company through electronic media. This study used a statutory research approach, with normative legal research—data collection techniques using literature study. The data was sourced from books and statutory documents. The results of this study indicated that the authority of a notary in making official reports using electronic media was regulated in Article 15 paragraph (3) of Law Number 2 of 2014 concerning Notary Positions, Article 77 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies, and Article 5 paragraph (1) of Law Number 19 of 2016 concerning Electronic Transaction Information. To conclude, minutes of the general meeting of shareholders held by teleconference or video conference still have legal force as an authentic deed.